New York City's captive work force: Remembering the prisoners who built Rikers Island. (March 2019) - Shanahan, Jarrod; Mooney, Jayne
Abstract: This article undertakes a "history of the present" as a means of intervening in current debate around the closure of the Rikers Island jail complex and its replacement with smaller "state of the art" jails. We argue that the telling of carceral history is potentially a powerful weapon capable of shaping unfolding events, as well as, helping to preserve the memory of those who have suffered from the practice of human caging. To this effect we reconstruct the history of the Rikers Island penal colony predating its officially-recognized opening in 1935; a history defined by the forced prison labour that was used to expand the island and construct the original penitentiary. We illustrate how the labour of these prisoners, lives on in the physical structure of Rikers, as well as in its scandalous carceral existence. In defiance of current efforts at piecemeal reform or of preserving the status quo, we offer this historical intervention as a means of problematizing the present effort to solve the problems of jails with more jails, suggesting instead that the past calls for more drastic action—an escape.